Hunting for Use-Wear - Matilda Siebrecht; Diederik Pomstra (EXARC Journal)
Investigating use-wear traces on antler and bone harpoon heads from the Dorset cultures using experimental archaeology. Harpoons are an essential part of the hunting toolkit amongst Inuit and have been integral to the material culture assemblage of Arctic groups for thousands of years. The pre-Inuit population known as the Dorset cultures (app. 800 BC–1300 AD) - also sometimes referred to as Tuniit - were highly dependent on a maritime subsistence with harpoon heads as one of the dominant artefact categories at Dorset sites. Although the use of these harpoons is known from historic ethnographic reports observing Inuit hunting techniques and comparison with modern harpoon styles, a preliminary study by Siebrecht suggests there is little evidence of this use found on the surface of archaeological harpoon heads in terms as microscopic use-wear. This contrasts with other studies investigating bone projectiles, which did identify traces of use after experimentation with replica objects. The present study therefore aims to investigate this disparity using several replica harpoon heads made of bone and antler to experimentally harpoon a seal carcass to determine the extent to which use-wear is formed when harpooning a marine mammal.